Evaluation of The Trading Strategy Using The "Moving Average" in The Iraqi Stock Market - Odah, Sabbar Thijeel (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This paper aims to evaluate the trading strategy using simple moving average with different lengths of "10 days, 20 days, 50 days, 100 days, 150 days, 200 days" on the Iraq Stock Exchange (ISX60) index during (109) trading days, and compare it with the simple buy and hold strategy. The findings show that, despite the Iraq Stock Exchange's lack of efficiency at the basic level, trading with moving averages may predict price movement and, after subtracting trading expenses, produces profits that are higher than those of the buy and hold strategy. Additionally, compared to other moving averages, the 20-day simple "moving average" is more predictive.